Anonymous
Anonymous asked in Science & MathematicsMathematics · 4 weeks ago

4x+x+4= 8x - 3x + 4 answer and?

Update:

and the equation 0.6(x+2) = 0.55 (2x + 3) plzz

4 Answers

Relevance
  • David
    Lv 7
    4 weeks ago

    1) 5x+4 = 5x+4 whereas x can take on any value

    2) 0.6(x+2) = 0.55(2x+3) 

    Multiply out the brackets: 0.6x+1.2 = 1.1x+1.65 

    Transposing terms: 0.6x - 1.1x = 1.65-1.2

    So: -0.5x = 0.45 

    Dividing both sides by -0.5: x = -0.9

  • 4 weeks ago

    4x + x + 4 = 8x - 3x + 4

    5x = 4 = 5x + 4

    0.6(x + 2) = 0.55 (2x + 3)

    1.2x + 1.2 = 1.1x + 1.65

    0.1x = 0.45

    x = 4.5 

  • 4 weeks ago

    Why, Anonymous?

  • 4 weeks ago

    Any number you want to plug in for X will make it work. Both sides come down to 5X so anything will work for X.

Still have questions? Get your answers by asking now.